Efektivitas Model Project Based Learning Berbantuan Media Mind Mapping terhadap Kemampuan Membaca Permulaan Siswa Kelas II SD 2 Gondangmanis - Elyana Rosyita; Khamdun Khamdun; Fatikhatun Najikhah (Lembaga Pengembangan Kinerja Dosen, 2026)
Early reading skills are fundamental competencies that must be mastered by elementary school students, as they serve as the foundation for future academic success. However, conventional teacher-centered instruction often fails to maximize students’ active engagement in learning. This study aims to analyze the effectiveness of the Project Based Learning model assisted by mind mapping media in improving the early reading skills of second-grade elementary students. This research employed a quantitative approach with an experimental design. The participants were second-grade students who received instruction through the Project Based Learning model assisted by mind mapping media. Data were collected using reading skill tests administered before and after the treatment. The data were analyzed to identify differences in students’ reading abilities following the implementation of the learning model. The findings indicate that the implementation of Project Based Learning assisted by mind mapping media has a positive effect on students’ early reading skills. The model promotes active student participation, enhances critical and creative thinking skills, and facilitates comprehension through structured visual representation of concepts. Furthermore, the learning environment becomes more interactive and meaningful, increasing students’ motivation to engage in reading activities. Therefore, the Project Based Learning model assisted by mind mapping media is recommended as an alternative instructional strategy to improve early reading skills in elementary schools.